MENGUKUR KINERJA KEPALA SEKOLAH DALAM MANAJEMEN KURIKULUM DAN PEMBELAJARAN - Mahrus (AN NAHDLIYYAH, 2023)
The current performance of school principals is very difficult and full of challenges, due to changes in laws and the curriculum which continues to be adjusted. This requires school principals to be able to realize curriculum objectives well so that obstacles can be minimized. It often happens in the field that school principals become targets of the community and students' parents because they cannot manage and carry out their duties properly, including curriculum management. If this is left unchecked it will have an impact on school administration and especially on students, therefore, school principals must be able to manage the curriculum well. In the world of education, performance measurement is carried out to measure the 3E level. Namely economy, efficiency and effectiveness. This research uses the library research method. Researchers read, examine and analyze various existing literature. Data collection techniques in this research refer to books, magazines and journals related to measuring school principal performance. The results of this research found that the performance measurement of school principals is seen from the economic level, efficiency and effectiveness of school work programs. Economic analysis of school performance programs can be measured through a comparison between input and actual input which is then given a qualitative meaning. Analysis of school performance efficiency can be divided into two types, namely external efficiency and internal efficiency, while analysis of the effectiveness of school performance is determined by the suitability of performance targets and realization input.